New bitongling regulates gut microbiota to predict angiogenesis in rheumatoid arthritis via the gut-joint axis: a deep neural network approach - Guan, Yin; Zhao, Xiaoqian; Lu, Yun; Zhang, Yue; Lu, Yan; Wang, Yue (Frontiers in Microbiology, 2025)
BackgroundRheumatoid arthritis (RA) is a persistent autoimmune disorder marked by inflammation and joint damage. Although current treatments, such as disease-modifying antirheumatic drugs (DMARDs), help control symptoms, they frequently cause substantial side effects, highlighting the urgent need for safer and more effective alternatives. Recent research indicates that gut microbiota might be pivotal in RA development through the “gut-joint axis,” presenting novel therapeutic possibilities.PurposeThis study seeks to explore the therapeutic potential of the traditional Chinese medicine (TCM) compound new bitongling (NBTL) for RA, with an emphasis on its capacity to regulate gut microbiota and suppress angiogenesis via the vascular endothelial growth factor (VEGF) signaling pathway.MethodsWe utilized a collagen-induced arthritis (CIA) rat model to assess the impact of NBTL. The study employed 16S ribosomal DNA (16S rDNA) sequencing to analyze gut microbiota composition, machine learning techniques to identify characteristic microbial taxa, and transcriptomic analysis (GSVA) to assess the impact on the VEGF signaling pathway. The findings were further validated through analysis with deep neural network models and in vivo/in vitro experiments, including western blot, immunofluorescence, and miRNA analysis.ResultsNBTL treatment markedly diminished inflammation in RA rats, evidenced by the reduced expression of TNF-α, IL-17, IL-6, and ASC in synovial tissues. Histopathological analysis confirmed alleviation of joint damage. Five characteristic microbial taxa, including f_Mycoplasmataceae, s_Metamycoplasma_sualvi, and g_Prevotellaceae_Ga6A1_group, were identified and associated with NBTL’s modulation of the VEGF pathway. Gene set variation analysis (GSVA) revealed significant downregulation of the VEGF signaling pathway following NBTL treatment. Subsequent experiments confirmed that NBTL inhibited VEGF and its receptors, VEGFR1 and VEGFR2, along with HIF-1α (hypoxia-inducible factor 1-alpha), thereby reducing angiogenesis. Additionally, NBTL upregulated miR-20a-5p and miR-223-3p, contributing to its anti-angiogenic effects.ConclusionNBTL exhibits significant therapeutic potential in RA by modulating gut microbiota and inhibiting the VEGF signaling pathway. These findings support NBTL’s use as a promising candidate for RA treatment, emphasizing the need for further research on its mechanisms and clinical application.